Organoleptic Test of Culled Laying Hens Meat with Marinating Unripe Papaya (Carica Papaya L.) Extract - Asih, Diah Reni; Ahmad, Miftahuddin; Anwar, Rohmatul; Subakti, Dwi; Ridwan Ali, Ahmad (Journal of Tropical Animal Science and Technology, 2025)
This study aims to determine the effect of meat of culled laying hens marinated with young papaya fruit. This study used a completely randomized design (CRD) with 4 treatments and 5 replicates. The treatments used in this study were P0 (without marination of young papaya fruit (control)), P1 (extract marination of young papaya with a percentage of 15%), P2 (extract marination of young papaya with a percentage of 30%), P3 (extract marination of young papaya with a percentage of 45%). The material used in this study was chicken breasts with a weight of 100 grams for each treatment. The variables observed in this study were organoleptic tests including aroma, color, and texture. Data obtained from the panelists' assessment were analyzed using Non-parametric analysis (Kruskal Wallis).  The results showed that the highest level of preference for the color variable was in treatment P3 with a value of 4.15, the highest texture was in P3 with a value of 3.6 while the highest aroma was in P0 with a value of 3.5. In conclusion, the meat of retired laying hens marinated with young papaya fruit showed that the best concentration was by giving 45% young papaya fruit extract which gave a significant effect (P <0.05) on color and texture. While for aroma it had no significant impact. Keywords: Aborted Layers, Marinated Young Papaya Fruit (Carica papaya L.), Organoleptic Test.